강점중심 집단프로그램의 효과성에 관한 메타분석연구 - 박정임(Jung-Im Park) (한국콘텐츠학회 논문지, 16(12), 2016)
This study was to examine the effectiveness of Strengths-Focused Group Program in Korea by using method of Meta-analysis. For the purpose of the study, master's theses, doctoral dissertations, and journal articles published in Korea up to August, 2016 were systematically reviewed. As a result, a total of 25 studies were eligible for the inclusion criteria. The mean effect sizes and test for homogeneity of effect size(Q-statistic) were analyzed by using Comprehensive Meta-Analysis software 2.0. The main findings of the study were as follows. First, the average effect sizes for Strengths-Focused Group Program were ES=1.400 of Psychological Wellbeing, ES= 1.104 of School Adjustment, ES= 0.908 of Self-Esteem. Second, the moderate variables of the effect size for Strengths-Focused Group Program was 'age' of ' a characteristic of the program', and 'the major of group leader'. Based on the study results, the research and practice implications were discussed. 본 연구에서는 국내에서 실시된 강점중심 집단프로그램의 효과크기를 통합하여 제시하고, 강점중심 집단프로그램의 효과적인 실천방안을 제시하기 위하여 메타분석을 실시하였다. 자료 수집은 메타분석의 대상선정기준에 따라 국내 석 박사 학위논문과 학술지 게재논문인 25편의 논문을 선정하여 분석하였다. 메타분석을 위해서는 CMA(Comprehensive Meta-Analysis) software 2.0을 사용하였다. 연구 결과는 다음과 같다. 첫째, 강점중심 집단프로그램의 평균효과크기를 살펴보면, 심리적 안녕감의 효과크기가 1.400으로 가장 높게 나타났고, 학교적응이 1.104, 자아존중감이 0.908로 나타나서 모두 큰 효과크기를 보였다. 둘째, 강점중심 집단프로그램의 실행에 따른 자아존중감과 심리적 안녕감의 효과크기가 조절변수(연령, 프로그램 특성, 총회기수, 진행자 전공)와 어떠한 관계가 있는가를 분석한 결과, 자아존중감에 있어서는 연령, 프로그램 특성, 진행자 전공, 총회기수, 심리적 안녕감에 있어서는 연령, 프로그램 특성, 진행자 전공이 통계적으로 유의미한 조절변수인 것으로 나타났다. 본 연구의 결과를 바탕으로 강점중심 집단프로그램의 이론적 실천적 함의와 전략을 제언하였다.